P090 The Effect of Workload, Sleep Deprivation and Time of Day on Simulated Driving Performance. (7th October 2021) - Marando, I; Matthews, R; Grosser, L; Yates, C; Banks, S
Abstract: Sustained operations expose individuals to long work periods, which deteriorates their ability to sustain attention. Biological factors, including sleep deprivation and time of day, have been shown to play a critical role in the ability to sustain attention. However, a gap in the literature exists regarding external factors, such as workload. Therefore, the aim of this study was to investigate the combined effect of sleep deprivation, time of day, and workload on sustained attention. Twenty-one participants (18–34y, 10 F) were exposed to 62 hours of sleep deprivation within a controlled laboratory environment. Every 8 hours, sustained attention was measured using a 30-minute monotonous driving task, and subjective workload was measured using the NASA-Task Load Index (TLX). Workload, defined as time on task was assessed by splitting the drive into two 15-minute loops. A mixed model ANOVA revealed significant main effects of day (sleep deprivation) and time of day on lane deviation, number of crashes, speed deviation and time outside the safe zone (all p<.001). There was a significant main effect of workload (time on task) on lane deviation (p=.042), indicating that a longer time on task resulted in greater lane deviation. NASA-TLX scores significantly increased with sleep deprivation (p<.001), indicating that subjective workload increased with sleep loss even though the task remained constant. Workload, sleep deprivation and time of day produced a deterioration in sustained attention. With this, countermeasures that not only consider sleep deprivation and time of day, but also workload (time on task) can be considered.